PENERAPAN GOOD GOVERNANCE TERHADAP KINERJA PEGAWAI DI KABUPATEN MAJENE PROVINSI SULAWESI BARAT - Wahyuni, Sri; Mahsyar, Abdul; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to determine the effect of implementing Good Governance on employee performance at the Population Service Office. The type of research used is quantitative research with an explanatory survey approach, the number of respondents was 45 people. Data collection techniques using observation, questionnaires and documentation. The results of the research show that there is an influence between the variables of implementing Good Governance and the performance of the Majene Regency Population and Civil Registry Service employees. The implementation of good governance is based on aspects of transparency, participation and accountability. percentage of 69.44%. Meanwhile, employee performance conditions show a percentage of 80%. The influence of implementing good governance on employee performance was presented at 30.3%, while 70% (100% - 30.3%) indicated that employee performance can also be influenced by other factors and causes outside the aspect of implementing good governance, such as aspects of work motivation, discipline, benefits. to organizational culture which also plays a role in optimizing employee performance.